Preparing health promotion behavior among adolescents at selected upazila in Bangladesh - Islam, Md. Tarequl; Gharami, Tumpa; Akter, Halima (Journal of Midwifery and Nursing, 2025)
Background: Health promotion behaviors are essential in shaping lifelong health habits among adolescents. In Bangladesh, adolescents encounter various health challenges, yet limited research exists on their health-promoting behaviors. Aim: This study investigated the health promotion behaviors of adolescents in Bangladesh.Methods: A cross-sectional study was conducted among 103 adolescents aged 12–18 years in Bangladesh. Participants were recruited using a convenient sampling method. Data were collected using a structured questionnaire designed to assess health behaviors and analyzed using SPSS version 26. Both descriptive and inferential statistical methods were applied.Results: The mean age of the participants was 15.12 years (SD = 0.771). The findings revealed significant relationships between health promotion behaviors and several demographic factors: mothers’ education level (F = 4.264, p = 0.003), fathers’ education level (F = 12.011, p = 0.000), fathers’ occupation (F = 6.455, p = 0.002), sources of health information (F = 4.814, p = 0.004), and family type (t = 2.212, p = 0.029). Conclusion: The study highlights significant associations between demographic characteristics and health promotion behaviors among adolescents in Bangladesh. To enhance these behaviors, interventions focusing on parental involvement, peer education, and better access to recreational facilities are recommended. Policymakers and health educators should prioritize these areas to improve health outcomes in this critical age group.